Mapping the implementation process for subsidized fertilizer distribution under Ghana’s Planting for Food and Jobs Program - Aberman, Noora-Lisa; Kufoalor, Doreen S.; Gilbert, Rachel (International Food Policy Research Institute, 2021)
Planting for Food and Jobs (PFJ) is Ghana’s flagship program for agricultural transformation and employment creation. Alongside other components, the program provides subsidized fertilizer, hybrid and open-pollinated seeds and other planting materials, improved extension services, and marketing support to smallholder farmers across the country. The objective of this study was to assess the implementation process of the PFJ input subsidy program in order to identify opportunities for strengthening the process. The study focused only on fertilizer distribution as a distinct complex process of importance, although some of the lessons will be applicable to other components of the PFJ program. The study applied the Process Net-Map method, a research approach that is particularly useful for assessing the coherence between formally prescribed procedures and how those procedures are implemented in practice, enabling the identification of inefficiencies and bottlenecks in a complex process. The implementation of the PFJ fertilizer subsidy program was mapped in interviews with key informants at national level and in six districts. Interviews with national-level stakeholders yielded important insights about the complex largely administrative process involved in the implementation of PFJ, which is generally unseen by beneficiaries. These administrative processes, however, have a considerable impact on the timeliness of the program and provide an outline of the intended implementation process at the local district level. The perspectives of farmers with regards to these processes were also investigated through in-depth interviews. Across the study districts we found some ambiguity and inconsistency in following the formally prescribed procedures for implementing the PFJ fertilizer subsidy program. While we found broad agreement among key informants and farmers that the program is meeting its objectives, some areas in which the implementation process for the PFJ fertilizer subsidy program could be improved are highlighted. These improvements will enhance the efficiency and impact of the program.